2009
DOI: 10.1037/a0013097
|View full text |Cite
|
Sign up to set email alerts
|

Teaching writing to high school students: A national survey.

Abstract: A random sample of language arts, social studies, and science high school teachers (N = 361; 53% women) from the United States were surveyed about what their students wrote, their use of evidence-based writing practices, the adaptations they made for weaker writers, how they assessed writing, their preparation to teach writing, beliefs about the importance of writing, and judgments about their students’ writing capabilities. The findings from this survey raised some concerns about the quality of high school wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
253
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(284 citation statements)
references
References 25 publications
20
253
2
9
Order By: Relevance
“…It is important to mention that these findings are consistent with the results reported in previous studies, like those of Graham and Perin (2007); Kiuhara, Graham, and Hawkin (2009);Ahlsen and Lundh (2008); McCarthey and Ro (2011); Grisham andWolsey (2011), andHaddad (2014). Most of their findings agree with the results of this research.…”
Section: Finding Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…It is important to mention that these findings are consistent with the results reported in previous studies, like those of Graham and Perin (2007); Kiuhara, Graham, and Hawkin (2009);Ahlsen and Lundh (2008); McCarthey and Ro (2011); Grisham andWolsey (2011), andHaddad (2014). Most of their findings agree with the results of this research.…”
Section: Finding Analysissupporting
confidence: 82%
“…They recommended that professional development for writing instruction be enhanced. Kiuhara, Graham, and Hawkin (2009) found that the most common writing activities that students engaged in were writing short answer responses to homework, responding to and summarizing the material they read, and completing worksheets,. The study revealed that these activities involved little extended analysis, interpretations or the process of writing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A more recent survey lends some insight into the nature of writing in many classes. Kiuhara, Graham, and Hawken (2009) found that when teachers assign writing in history classrooms, the focus typically involves summary of information. Yet a focus on summary writing in history inhibits students' historical reasoning because history is interpretive and relies on the reconciliation of multiple sources of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, legible and stylish handwriting has been an indicator of one's level of education and his/her social status (Blazer 2010). Although today it is generally thought that cursive slant handwriting has started to lose its importance (Blazer, 2010;Armstrong, 2014;Puranik et al, 2014), teaching of handwriting skills especially in primary and secondary school programs keeps its importance despite arguments over the style of writing (cursive or manuscript) (Graham et al, 2014;Kiuhara et al 2009;Schwellnus et al 2012;Sharp & Titus, 2016;Ziviani & Watson-Will, 1998).…”
Section: Writing Speedmentioning
confidence: 99%